Tool Support for System-Theoretic Process Analysis - Petzold, Jette; von Hanxleden, Reinhard (Electronic Communications of the EASST, 2023)
Hazard analysis techniques such as System-Theoretic Process Analysis (STPA) are used to guarantee the safety of safety-critical systems. Our goal is to improve the tool support for STPA. The preliminary result is the PASTA Visual Studio Code (VSCode) Extension that provides verification checks and diagrams. PASTA uses elkjs to layout the diagrams and Sprotty to draw them. We evaluate PASTA by recreating the ROLFER analysis. In the future we plan to further evaluate whether PASTA improves upon existing tools and to add more features such as reevaluation suggestions, model checking, and support for other risk analysis techniques.